(untitled) (Herald of the National Children’s Medical Center, 2025)
Child disability is one of the most pressing problems of modern society. According to data from the United Nations, WHO, and UNICEF, there were 140 million children with disabilities worldwide in 2006, and today their number exceeds 240 million. Experts from the World Health Organization estimate that the proportion of severe childhood disability among children is about 2%. The growth and high prevalence of childhood disability call for the improvement of prevention measures based on the study of risk factors and their impact.